Development of photo-reversible aqueous biphasic systems - Fonseca, Ana Beatriz Lopes (2023)
The separation and purification of added-value (bio)compounds is one of the most expensive steps, where about 60-70 % of the total costs of the process can be attributed to this step. To overcome this drawback, aqueous biphasic systems (ABS) have been studied as alternative platforms for the separation and/or purification of a wide variety of compounds. These liquid-liquid systems are composed of water, avoiding the use of organic solvents and, consequently, being more environmentally benign and biocompatible. Recently, reversible ABS, i.e., ABS that can change from a monophasic state to a biphasic one (and vice-versa) through the application of stimuli, have been proposed. This reversibility allows the integration of several steps and, consequently, a reduction in costs and an increase in the speed of the process. The stimuli reported in the literature to develop reversible ABS are temperature, pH, gas flushing and, more recently, light. Flavylium derivatives, in particular 4’,7-dihydroxyflavylium chloride (DHF), is one of the most studied and characterized molecules with a photochromic effect at a slightly acidic pH. Thus, in this work, it was created an ABS composed of two polymers, polyethylene glycol (PEG) and sodium polyacrylate (NaPA), and DHF, in small quantities. Different molecular weights of PEG and two concentrations of DHF were tested, 1×10-4 M and 1×10-6 M. With the higher concentration, the colours of the ABS became too intense, turning difficult to observe the change in the phases. Having optimized the DHF concentration, it was used an UV light at 365 nm to test its effect on the photoreversible behaviour of ABS. Of the studied DHF concentrations, it was observed that at the lowest DHF concentration, light did not have the desire effect of facilitating phase separation, creating a small photo-reversible region to allow the choice of mixture points with confidence. An intermediated concentration of 1×10-5 M of DHF was then tested. Using this intermediate concentration, it was possible to create a wider photo-reversible region, from which a mixture point was chosen. This mixture point was biphasic when under UV light for 3 min and monophasic when in the dark for 2h, thus creating a proof of concept for a photo-reversible ABS. More studies on this ABS should be carried out in the future, namely the optimization of the ABS composition and parameters such as pH and temperature, so that its applications in real photo(bio)catalysis processes can be further studied.